An Analysis of the Online Registration System at Caruban Hospital in 2020 - Iin Suwandari; Ratna Wardani (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Backgorund.Information technology can support medical record services in hospitals, especially in patient registration places. The implementation of this technology can be done by applying an online registration system. This system will be able to save waiting time for patients to register Purpose. This study aims to determine the implementation of the online registration system at Caruban Regional Public Hospital, Madiun District Method. This study uses a qualitative method with a case study approach. The sampling technique used was purposive sampling with an informant of 6 registration officers and 20 patients. Result.. The online registration system starts in July 2020. The results of the interview show that the system has not been optimally used. Some of the problems are that many patients are elderly so they are not technologically literate, geographic location of the patient causes difficult signals, the patient's electronic devices, and the lack of socialization from registration officer to patients. Patients know only from brochures or banners, so patients do not know the steps to use the system in detail Conclussion. The online registration system at Caruban Regional public Hospital is not optimal because there are several problems, such as the large number of elderly patients, the reluctance of the community to try to use the system and the lack of socialization